Culturally Responsive English Storytelling to Support Social-Emotional Learning in Primary Education - Nur Cahya; Elfi Churnia (Jurnal Generasi Ceria Indonesia, 2026)
Primary education requires learning practices that support children’s linguistic, cultural, and social-emotional development. English storytelling is often used to engage young learners through meaningful language input, imagination, and interaction. However, its potential to connect language learning with students’ cultural experiences and social-emotional learning remains insufficiently synthesized. This article examines culturally responsive English storytelling as a pedagogical approach for supporting social-emotional learning in primary education. Research Method: This study employed an integrative literature review design. Relevant theoretical, empirical, and review-based sources on culturally responsive pedagogy, English storytelling, children’s literature, picturebooks, and social-emotional learning were identified, evaluated, and synthesized thematically. The analysis focused on conceptual relationships among culture, English storytelling, and social-emotional learning in primary classroom contexts. Research Results: The synthesis resulted in four themes: storytelling as meaningful English language input, cultural narratives as identity-affirming pedagogy, storytelling as a medium for social-emotional learning, and a proposed framework for culturally responsive English storytelling. The findings suggest that culturally meaningful stories may support children’s English engagement while also encouraging reflection on emotions, empathy, relationships, moral choices, and responsible decision-making. Conclusion: Culturally responsive English storytelling offers a promising classroom-based approach for integrating English learning with cultural identity and social-emotional development. The proposed framework may support holistic child development, although future empirical studies are needed to examine its implementation and impact.